Problems and prospects of CBD horizontal and vertical expansion in mining areas: the case of Kwekwe, Zimbabwe - Chikwetu, Milton; Innocent, Chirisa (Faculty of Social Sciences and Humanities, UKM,Bangi, 2014)
This study explores and discusses the constraints and prospects of horizontal and vertical expansion of Zimbabwe’s Kwekwe Central Business Expansion (CBD). Particular emphasis is put on assessing the impacts of gold mining on the constructability of the CBD. The study emanates from the view that the CBD of Kwekwe seats on mining shafts and tunnels where gold mining activities have been done and, in some instances, still being practised. The underground and open cast mining processes have immensely disturbed the stability and natural form of the ground. In obtaining data, the study adopted both qualitative and quantitative methods in which a survey was conducted in the CBD. Interviews were also conducted with the local authority, estate developers and mine operators. The study shows that various stakeholders in the CBD are aware of the impact of mines especially the likelihood of ground subsidence. One important aspect which can be noted is that mining activities preceded the development of the City of Kwekwe thus posing a great challenge in as far as expanding the CBD is concerned. Illegal gold panners present another great threat to the CBD as they tend to destroy the reinforcements of underground mine tunnels. To avert this peril it is imperative that the local authority put in place a monitoring mechanism such as seismographs to detect possible seismic events in the CBD. There is also a need for all stakeholders in the CBD to engage in a memorandum of understanding regarding the issue of illegal gold panning to promote sustainable growth of the CBD.